Pengaruh standard profesionalisme guru ke atas kemenjadian murid di Daerah Pendang - Mohd Saiful Islam, Ghazali (2020)
The main purpose of this study was to identify the influence of professionalism standards implemented by administrators and teachers in relation to student outcomes in schools especially in the elements related to professionalism standards about knowledge, values and practices. The study involved a sample of 210 administrators and teachers of the National School in Pendang District. The study variables were tested using descriptive statistical analysis and inference statistical analysis involving Pearson Correlation and Multiple Regression. This study found that the standard of professionalism has a significant relationship with the student enrolment in national schools. The value of professionalism has a high correlation of 29.3% to student outcomes. The findings also showed that knowledge of professionalism contributed 27.6% and practice of professionalism contributed 26.3% to student establishment Accordingly, the findings of the study suggest that relevant parties may consider broader opportunities for new administrators and teachers to gain a deeper understanding of standards of professionalism including knowledge, values and practices to student outcomes.